PENGARUH BRAND IMAGE DAN DESAIN PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK BATA SHOES DI KOTA MEDAN - Sai Vinodhini; Nasib, Nasib; Ahmad Fadli (Jurnal Mahkota Bisnis (Makbis), 2022)
The purpose of this study is to understand and analyze the influence of brand image and product design on the purchasing decisions of Bata Shoes products in Medan, both partially and simultaneously. The population for this study consists of the average customers of Bata Shoes at Ringroad Medan. The sampling method used is Accidental Sampling, a technique where the sample is determined based on chance encounters. The author selected a sample of 120 customers of Bata Shoes Ringroad. The study results indicate a positive and significant influence of brand image on the purchasing decisions of Bata Shoes products, as evidenced by a t-value of 4.897, which is greater than the critical t-value of 1.980 (p-value = 0.000), where the significance level is less than α = 0.05. Similarly, there is a positive and significant influence of product design on purchasing decisions, with a t-value of 4.619, also greater than the critical t-value of 1.980 (p-value = 0.000), where the significance level is less than α = 0.05. Simultaneously, it was found that there is a positive and significant influence of both brand image and product design on the purchasing decisions of Bata Shoes products, as indicated by an F-value of 35.656, which is greater than the critical F-value of 3.07, with a p-value of 0.000, which is less than α = 0.05. Based on the coefficient of determination test, the R² value is 0.379, meaning that 37.9% of the factors affecting purchasing decisions can be explained by brand image and product design, while the remaining 62.1% can be attributed to other factors not examined in this study